Effect of dental intervention on improvements in metabolic syndrome patients: a randomized controlled clinical trial - Midori Doke; Yuriko Komagamine; Manabu Kanazawa; Maiko Iwaki; Hiroyuki Suzuki; Yasunari Miyazaki; Tetsuya Mizuno; Kaori Okayasu; Shunsuke Minakuchi (BMC, 2021)
Abstract Background Metabolic syndrome (MetS), caused by the accumulation of visceral fat, is considered a major cause of cardiovascular disease. This randomized controlled trial aimed to clarify the effect of dental intervention, including prosthodontics and/or periodontal treatment, combined with dietary and exercise guidance on MetS. Methods In total, 112 patients who met the Japanese waist circumference criteria of MetS were recruited. The intervention group (ITG) received dental intervention along with dietary and exercise guidance, while the control group (CTG) received dietary and exercise guidance alone. Three outcome measurements were obtained before intervention (BL), 1 month after intervention (1M), and 3 months after intervention (3M). Results Body water rate (p = 0.043) was significantly higher in ITG than in CTG at 1M. Simultaneously, fasting blood sugar level (p = 0.098) tended to be lower in ITG than in CTG. Lean mass (p = 0.037) and muscle mass (p = 0.035) were significantly higher and body weight (p = 0.044) significantly lower in ITG than in CTG at 3M. Body mass index (p = 0.052) tended to be lower in ITG than in CTG. Conclusions Dental intervention combined with lifestyle guidance may improve anthropometric status and reduce the risk of MetS. Trial registration University Hospital Medical Information Network Center Unique UMIN000022753. https://upload.umin.ac.jp/cgi-open-bin/ctr/ctr_view.cgi?recptno=R000026176 .